An effective method for improving software quality by automated test generation technique - Rao S, Srinivasa; Reddy T, Karthik; Sai N, Prasanna; Krishna Ch, Vamsi (International Journal of Engineering and Technology, 2017)
The general undertaking of the product building is to guarantee conveyance of superb programming to the end client. To ensure great programming, it is required to test programming. Testing is a critical constituent of programming building. In programming testing there are number of fundamental issues like compelling age of experiments, prioritization of experiments which should be handled. This mechanized test structure predominantly relies upon these four angles: test system, experiment age, test execution and test assessment. Test methodology is an accumulation of systems that decides the testing way to deal with be trailed by the testing group. The experiment age alludes to the age of experiments in light of the given application. The test execution briefs about the execution of those tests at that point contrasting the normal outcome and genuine outcome. The test assessment explores the experiments and causes us to produce test rundown report and programming quality confirmation report consequently. The aim of delivering this device is to produce test cases naturally and to diminish the cost of testing notwithstanding collect the season of determining experiments physically. Subsequently this framework enhances general nature of the product.